Presynaptic Capacitance Measurements and Ca(2)(+) Uncaging Reveal Submillisecond Exocytosis Kinetics and Characterize the Ca(2)(+) Sensitivity of Vesicle Pool Depletion at a Fast CNS Synapse - Wölfel, Markus (J Neurosci, 2003)
The intracellular Ca(2+) sensitivity of synaptic vesicle fusion is an important determinant of transmitter release probability, but it is unknown for most CNS synapses. We combined whole-cell membrane capacitance measurements and Ca(2+) uncaging at the large calyx of Held nerve terminals to determine the Ca(2+) sensitivity of synaptic vesicle fusion at a glutamatergic CNS synapse, independent of recording EPSCs. Capacitance increases measured 30-50 msec after elevating the intracellular Ca(2+) concentration ([Ca(2+)](i)) by Ca(2+) uncaging were half-maximal at ∼5 μm [Ca(2+)](i). At 10 μm [Ca(2+)](i), capacitance increases reached maximal values (256 ± 125 fF; mean ± SD), indicating the depletion of an average pool of ∼4000 readily releasable vesicles. Vesicle pool depletion was confirmed in cross-depletion experiments, in which capacitance responses were measured after Ca(2+) uncaging, or after combined stimuli of prolonged presynaptic depolarizations and Ca(2+) uncaging. To analyze the Ca(2+)-dependent rates of vesicle pool depletion, the capacitance rise after Ca(2+) uncaging was fitted with single- or double-exponential functions. The fast time constants of double-exponential fits, and the time constants of single-exponential fits were 2-3 msec at 10-15 μm [Ca(2+)](i) and reached submillisecond values at 30 μm [Ca(2+)](i). These results suggest that three to five readily releasable vesicles can fuse within <1 msec at each active zone of a calyx of Held, given that [Ca(2+)](i) rises sufficiently high. Submillisecond kinetics of exocytosis are reached at significantly lower [Ca(2+)](i) than at ribbon-type sensory synapses previously investigated by capacitance measurements.